2014
DOI: 10.3354/meps10964
|View full text |Cite
|
Sign up to set email alerts
|

Thinning of kelp canopy modifies understory assemblages: the importance of canopy density

Abstract: Kelp forests in southeastern Australia form canopies that support complex understory assemblages. Predicted levels of climate change in this region are likely to impact the health and distribution of these forests, potentially resulting in large-scale reductions in canopy cover. This study determined the impacts of a permanent reduction in canopy cover of the dominant kelp in this region, Ecklonia radiata, on the structure of understory algal and sessile invertebrate community assemblages. Changes in assemblag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
46
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 73 publications
3
46
3
Order By: Relevance
“…Importantly, recruitment was notably greater in the presence of adult sporophytes. This is contrary to the studies of Carnell and Keough [49] and Flukes, Johnson and Wright [50], who showed greater recruitment of E . radiata into patches cleared of canopy-forming algae.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Importantly, recruitment was notably greater in the presence of adult sporophytes. This is contrary to the studies of Carnell and Keough [49] and Flukes, Johnson and Wright [50], who showed greater recruitment of E . radiata into patches cleared of canopy-forming algae.…”
Section: Discussioncontrasting
confidence: 99%
“…The first addresses the effects of the scale of the kelp bed patch and extent of intraspecific competition. Carnell and Keough [49] and Flukes, Johnson and Wright [50] worked in large beds of dense kelp where the benthos was heavily shaded (>100% canopy cover) and there was (ostensibly) an abundance of spore production. In contrast, since the small patch reefs initiated in the ‘kelp bed state’ supported only 3 adult sporophytes defining 50% canopy cover, light levels on these patches were likely higher than on larger kelp patches with a similar density of individuals (C. Layton, unpublished data), and thus the effects of intraspecific competition are likely much reduced relative to larger kelp bed patches.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…data). Thus although canopy thinning in the field often results in an increase in juvenile sporophyte abundance (Kirkman 1981, Kennelly 1987, Flukes et al 2014, the response of microscopic and juvenile sporophytes to the increased light appears complex and likely to interact with other environmental stressors. There is high phenotypic plasticity in E. radiata to environmental factors Thomsen 2005, Fowler-Walker et al 2006), but the possible adaptive responses are not known.…”
mentioning
confidence: 99%
“…The predictive ability of the model was not improved by considering other non-climatic proxies of coastal urbanization: local water temperature, turbidity or nitrogen concentration. been shown as the prelude to changes in canopy assemblages and associated species (Flukes, Johnson, & Wright, 2014). Once established, turfs can also begin to alter the chemical microenvironment of rocky substrate to have negative impacts on subsequent canopy recruitment (Layton et al, 2019).…”
Section: Re Sultsmentioning
confidence: 99%